2006
DOI: 10.1193/1.2360907
|View full text |Cite
|
Sign up to set email alerts
|

Code Approaches to Seismic Design of Masonry-Infilled Reinforced ConcreteFrames: A State-of-the-Art Review

Abstract: Masonry infill ͑MI͒ walls are remarkable in increasing the initial stiffness of reinforced concrete ͑RC͒ frames, and being the stiffer component, attract most of the lateral seismic shear forces on buildings, thereby reducing the demand on the RC frame members. However, behavior of MI is difficult to predict because of significant variations in material properties and because of failure modes that are brittle in nature. As a result, MI walls have often been treated as nonstructural elements in buildings, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 115 publications
(56 citation statements)
references
References 5 publications
2
53
0
1
Order By: Relevance
“…Openings in infills are not looked upon in detail by most seismic codes [37]. Some codes use thumb rules for consideration of openings in masonry infills, for example, according to Eurocode8 [38], only the solid walls or walls with a single door or window opening are assumed to be imparting any significant strength to the structure.…”
Section: Infilled Frames With Openings and Seismic Codesmentioning
confidence: 99%
“…Openings in infills are not looked upon in detail by most seismic codes [37]. Some codes use thumb rules for consideration of openings in masonry infills, for example, according to Eurocode8 [38], only the solid walls or walls with a single door or window opening are assumed to be imparting any significant strength to the structure.…”
Section: Infilled Frames With Openings and Seismic Codesmentioning
confidence: 99%
“…Despite large amount of research performed in this field both experimentally and numerically in the last few decades, present seismic codes such as (IS1893 2002) [1] provide limited guidance which may not be adequate for the varying properties of infill. Kaushik (2006) [2] made comparative study among the different seismic codes and found inconsistency in the consideration of infill and reported that most codes do not consider infill due to its brittle nature of failure and lack of adequate information.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, presence of these openings decreases stiffness and strength of infilled frames. A review of analysis and design provisions related to masonry infilled RC frames in seismic design codes of different countries shows that only a few codes have considered the effect of infill in analysis and design of masonry infilled RC frames (Kaushik et al 2006). On the other hand, the stiffness and strength of the infilled frames with opening are not taken care of by most of the codes.…”
Section: Introductionmentioning
confidence: 99%